Bestiarium Judaicum : unnatural histories of the Jews - Geller, Jay, 1953- (Fordham University Press, 2018)
Given the vast inventory of verbal and visual images of nonhuman animals disseminated for millennia to debase and bestialize Jews (the Bestiarium Judaicum), this work asks: What is at play when Jewish-identified writers employ such figures in their narratives and poems? Bringing together Jewish cultural studies, examining how Jews have negotiated Jew-Gentile difference, and critical animal studies, analyzing the functions served by asserting human-animal difference, this monograph focuses on the writings of primarily Germanophone authors, including Sigmund Freud, Heinrich Heine, Franz Kafka, Gertrud Kolmar, H. Leivick, Felix Salten, and Curt Siodmak. It ferrets out of their nonhuman-animal constructions their responses to the bestial answers upon which the Jewish and animal questions converged and by which varieties of the species 'Jew' were depicted.